LIS Education in an Interdisciplinary Frame: Integrating Digital Media into the Ethics of Digital Personhood - Karno, Valerio; Roth, Adam David (DESIDOC Journal of Library & Information Technology, 2016)
This article explores the ways in which the Graduate School of Library and Information Studies at the University of Rhode Island integrates digital media into its curricula and research as part of its ongoing interdisciplinary framework. Suggesting it is incumbent on LIS educators to both teach technological skills and examine digital media tools as objects of intellectual inquiry, this article contends that LIS education must consider core epistemological questions which inform the field and address significant philosophical and cultural questions regarding our digital selves. The article considers how we can attend to issues of equity for diverse populations, and work towards understanding the assumptions inherent in digital spaces and technological tools which are guiding the creation of our digital borders.